The inverse relationship between prostate specific antigen (PSA) and obesity. Issue 11 (November 2018) - Aref, Adel T; Vincent, Andrew D; O'Callaghan, Michael E; Martin, Sean A; Sutherland, Peter D; Hoy, Andrew J; Butler, Lisa M; Wittert, Gary A
Abstract : Obese men have lower serum prostate-specific antigen (PSA) than comparably aged lean men, but the underlying mechanism remains unclear. The aim of this study was to determine the effect of obesity on PSA and the potential contributing mechanisms. A cohort of 1195 men aged 35 years and over at recruitment, with demographic, anthropometric (BMI, waist circumference (WC)) and serum hormone (serum testosterone, estradiol (E2)) PSA and hematology assessments obtained over two waves was assessed. Men with a history of prostate cancer or missing PSA were excluded, leaving 970 men for the final analysis. Mixed-effects regressions and mediation analyses adjusting for hormonal and volumetric factors explore the potential mechanisms relating obesity to PSA. After adjusting for age, PSA levels were lower in men with greater WC ( P  = 0.001). In a multivariable model including WC, age, E2/testosterone and PlasV as predictors, no statistically significant associations were observed between with PSA and either WC ( P  = 0.36) or PlasV ( P  = 0.49), while strong associations were observed with both E2/testosterone ( P  < 0.001) and age ( P  < 0.001). In the mediation analyses with PlasV as the mediator, the average causal mediation effect (ACME) explained roughly 20% of the total effect of WC on PSA ( P  = 0.31), while when E2/testosterone is a mediator, the ACME explained roughly 50% of the effect ( P  < 0.001). Our findings indicate that lower PSA levels in obese men, as compared to normal weight men, can be explained both by hormonal changes (elevated E2/testosterone ratio) and hemodilution. Hormonal factors therefore represent a substantial but underappreciated mediating pathway.